Modos de aplicação de zinco na nutricão e na produção de massa seca de plantas de trigo - Orioli Junior, Valdeci [UNESP]; Prado, Renato de Mello [UNESP]; Leonel, Cristian Luarte [UNESP]; Cazetta, Disnei Amelio [UNESP]; da Silveira, Cesar Martoreli [UNESP]; Barbosa Queiroz, Rafaela Josemara [UNESP]; Aires da Gama Bastos, Joani Cristina Hungaro [UNESP] (Soc Chilena Ciência Suelo, 2008)
Zinc application methods can affect the nutrition and the initial development of the wheat. Thus, the aim of this work was to analyze the different ways of Zn application in the soil, on nutrition and on dry matter production. A completely randomized experimental design with four replications was used. The experiment was composed by the following Zn application treatments: control (no zinc application); soil incorporation, furrow located, seeds treatment and leaf pulverization. The experimental unit was composed of a pot filled with 7 L of soil. Morphological traits for each plant were determined on 52 days after emergence by the evaluations of plant height, internodes number, tillers number and aerial part dry matter. Still, the soil and plant chemical analysis was accomplished. The furrow located method provided larger concentrations of the micronutrient available. The zinc application methods did not influence the initial growth of the wheat plants. The zinc concentration in leaves was influenced by the different application methods, being the leaf pulverization the one that was caused the largest zinc accumulation on aerial part dry matter.

Os modos de aplicação de zinco podem atetar a nutrição e o desenvolvimento inicial da cultura do trigo. Assim, o presente trabalho teve por objetivo avaliar os modos de aplicação de Zn no solo, na nutrição e na produção de materia seca do trigo. O delineamento experimental utilizado foi inteiramente casualizado, com quatro repetições. Os tratamentos utilizados foram: Zn incorporado no solo, localizado no sulco, tratamento de sementes, via pulverização foliar, além da testemunha (sem aplicação de Zn). A unidade experimental foi composta de um vaso preenchido com 7 L de solo (LATOSSOLO VERMELHO distrófico). Aos 52 dias após a emergência, avaliou-se a altura de plantas, número de entrenós, número de perfilhos e massa seca da parte aérea. Ainda, realizou-se a análise quí'92mica do solo e da planta. O modo de aplicação de zinco no solo de forma localizada proporcionou maiores concentrações do micronutriente disponível. Os modos de aplicação de Zn, não influenciaram o crescimento inicial das plantas de trigo. O teor foliar de Zn foi influenciado pelos diferentes métodos de aplicação, sendo a aplicação foliar a que ocasionou o maior acúmulo do nutriente na massa seca da parte aérea do trigo.
Methods of zinc application in the nutrition and production of wheat plant dry matter
Keywords: Triticum aestivum L.; plants nutrition; application forms; micronutrient; greenhouse